A Category With Multiple Centers: The Case of the Ukrainian Verbal Prefix Za- - Starko, Vasyl (East European Journal of Psycholinguistics, 2022)
The present study aims to reconstruct the structure of the Ukrainian verbal prefix za- as a category. Cognitive modeling and the network approach are used to this end, similarly to other works within the Cognitive Linguistics paradigm (Janda 1985, 1986), (Sokolova & Endresen, 2017), (Tabakowska, 2003). The modeling phase is preceded by an analysis of a large sample of Ukrainian za- verbs, which are grouped into semantic blocks based on shared semantic content. These blocks are then mapped onto a network of conceptual schemas, which includes such prominent centers as CURVE and APPEAR. The latter and several other nodes are shown to be modifications of CURVE with the links between them constituting family resemblances (Wittgenstein, 2009). The conceptual schema APPEAR is actively used by native speakers to coin new inchoative za- verbs in Ukrainian and several Slavic languages, which means that conscious (Type 2) categorization (Starko, 2014) is employed. This and other considerations suggest that APPEAR is a psychologically real conceptual entity in its own right. Thus, an argument is made in favor of a bifocal, rather than unicentric, topology of the za- network, which is contrary to the popular assumption about the existence of a single central element (prototype) from which all other network nodes are derived in what is called “radial structure” or “radical category” (Lakoff, 1987). The a priori assumption in the study of categories should be that they may be unicentric or pluricentric. Acknowledgements This research was supported by a grant from the Humanities Faculty of the Ukrainian Catholic University (Lviv, Ukraine).